The archaeology of overburden: Method within the madness at Švédův Stůl, Czech Republic. (August 2021) - Wright, Duncan; Hughes, Philip; Skopal, Nicholas; Kmošek, Matěj; Way, Amy; Sullivan, Marjorie; Lisá, Lenka; Ricardi, Pamela; Škrdla, Petr; Nejman, Ladislav; Gadd, Patricia; Fišáková, Miriam Nývltová; et al.
Abstract: In the 19th and early to mid-20th centuries, a rush to better understand the European Palaeolithic led to the substantive removal of deposits from limestone caves. In the 21st century the situation has changed. Many caves are now excavated, leaving behind a human-made environment of diminished cave sediments and large spoil heaps, with the latter now targeted by those searching for artefacts missed during the original excavations. In an age in which archaeologists are increasingly attempting to balance their roles as cultural heritage educators and destroyers, the question remains - how much do we know about the taphonomy of these features? In this paper we report results from the excavation of a large spoil heap outside Švédův Stůl Cave, in the Moravian Karst region of Czech Republic. Results show heterogeneous sediment formation (revealed primarily through their field characteristics and ED-XRF and Itrax geochemical analyses) and patterns in artefact distributions (evident through assessment of Iron Age, Neolithic and modern artefacts) and faunal remains. This allows partial context to be provided for some artefacts and a methodology to be developed for excavation of overburden. Highlights: Identify intact contexts within archaeological spoil. Insight into hominin activity in Czech Republic during mid-late Palaeolithic. Demonstrate how XRF (ED-XRF and Itrax) may unravel complex sediment histories. Provide a new methodology for excavating overburden. Flag urgent need to apply these methods before excavation destroys these features.